2014
DOI: 10.1089/neu.2013.3206
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Serotonergic Medications on Locomotor Performance in Humans with Incomplete Spinal Cord Injury

Abstract: Incomplete spinal cord injury (iSCI) often results in significant motor impairments that lead to decreased functional mobility. Loss of descending serotonergic (5HT) input to spinal circuits is thought to contribute to motor impairments, with enhanced motor function demonstrated through augmentation of 5HT signaling. However, the presence of spastic motor behaviors in SCI is attributed, in part, to changes in spinal 5HT receptors that augment their activity in the absence of 5HT, although data demonstrating mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 60 publications
1
17
0
3
Order By: Relevance
“…Regardless, the present data are consistent with selected studies in animal models 52 and humans of neurologic injury (SCI) 51 indicating no immediate improvements in locomotion function with single-dose enhancement of 5-HT transmission. These findings are of clinical interest because previous data suggest improvements in motor function after prolonged SSRI use, although greater changes were observed in upper versus lower limbs.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Regardless, the present data are consistent with selected studies in animal models 52 and humans of neurologic injury (SCI) 51 indicating no immediate improvements in locomotion function with single-dose enhancement of 5-HT transmission. These findings are of clinical interest because previous data suggest improvements in motor function after prolonged SSRI use, although greater changes were observed in upper versus lower limbs.…”
supporting
confidence: 87%
“…While locomotion is associated with increased 5-HT activity, the nonsignificant increases in strength with significant gains in spasticity could have limited functional performance. More detailed biomechanical and electromyographic analyses during walking after SSRIs are necessary to identify specific locomotor changes, 51 accessed by following the link in the citation at the bottom of the page.…”
Section: Minimal Changes In Single Mvcs or Clinical Assessmentsmentioning
confidence: 99%
“…Different implications thereof were mentioned, ranging from considerable baseline variability, which could not be accounted for, to limited generalizability of the results, decreased power, and the need for replication in larger samples . Seventeen studies (10%) stated a rule‐of‐thumb like justification for the choice of a particular statistical approach, mainly that nonparametric methods were used instead of parametric approaches due to the small sample size . However, no study was found where the authors provided a theoretically sound reason (eg, by referring to a simulation study, which indicates a good performance in small sample settings).…”
Section: Resultsmentioning
confidence: 99%
“…46,47 Seventeen studies (10%) stated a rule-of-thumb like justification for the choice of a particular statistical approach, mainly that nonparametric methods were used instead of parametric approaches due to the small sample size. [48][49][50][51][52][53][54][55] However, no study was found where the authors provided a theoretically sound reason (eg, by referring to a simulation study, which indicates a good performance in small sample settings).…”
Section: Statistical Methods and Mentioning Potential Problemsmentioning
confidence: 99%
“…The cDNA was 10-fold serially diluted to seven concentrations for the standard curve. sensory and motor function is also not satisfaction [4,5]. Hence, it is also attractive to study on the mechanism of SCI to find the valid strategy for further functional recovery.…”
Section: Reverse Transcription Pcrmentioning
confidence: 99%